Correlation of Glacier ELA/Snowlines & Temperature Station data with ERA5 Temperature and Wind Speed, 1979 to 2017 - Audet, Alexander; Putnam, Aaron E; Russell, Joellen; Lorrey, Andrew; Denton, George H (PANGAEA, 2022)
This dataset contains the gridded correlation results from a study that sought to better understand the climatic footprint monitored by antipodal mid-latitude glacier populations. Understanding the links between glaciers and climate is critical for accurately interpreting contemporary cryosphere changes, and interrogating the causes of past glacier behavior. However, work is still needed to refine the extent to which they capture regional to hemisphere-scale atmospheric processes. A Pearson's correlation was performed between yearly summer seasonal data from the ERA5 gridded reconstructions of global temperature and wind changes on each available ERA5 pressure level and yearly glacier snowline/ELA elevations in the Southern Alps of New Zealand and in the European Alps. December-Febuary austral summer data was correlated with the Southern Alps records and June-August Northern Hemisphere summer data was correlated with the European Alps. The ERA5 input dataset was regridded onto a new monthly axis representing the true month lengths. Then the weighted seasonal average (December-February and June-August) was calculated. Individuals glaciers with Equilibrium Line Altitude (ELA; European Alps) and End of Summer Snowlines (EOSS; Southern Alps) were selected with respective records covering at least 80% of the 1979-2017/15 analysis period. The records from each glacier were then standardized and an EOF analysis was performed to obtain each location's First Principle Component for input into the Pearson's Correlation. A nearly identical set of analyses was performed using weather stations temperature data instead of glacier ELA/snowlines. The New Zealand station equivalent is from the National Institute of Water and Atmospheric Research (NIWA) New Zealand seven-station (NZ7S) series. The European Alps equivalent is from the HistAlp regional weather station syntheses. This companion analysis allows the glacier's ability to record the climate to be compared to that of meteorological instruments.
Keywords: Alps; correlation; ERA5; European Alps; Glacier; New Zealand; Southern Hemisphere Westerly Winds; Westerlies